Lung lobe torsion in dogs: 52 cases (2005–2017). Issue 8 (10th October 2018) - Park, Karen M.; Grimes, Janet A.; Wallace, Mandy L.; Sterman, Allyson A.; Thieman Mankin, Kelley M.; Campbell, Bonnie G.; Flannery, Erin E.; Milovancev, Milan; Mathews, Kyle G.; Schmiedt, Chad W.
Abstract: Objective: To report outcomes and risk factors for mortality in dogs that underwent surgical management of lung lobe torsion. Study design: Retrospective case series from 5 veterinary teaching hospitals (2005–2017). Animals: Fifty dogs with 52 instances of lung lobe torsion. Methods: Data collected from medical records included signalment, clinical findings, results of clinicopathologic testing and diagnostic imaging, surgical treatment, lung lobe affected, intraoperative and postoperative complications, histopathologic and microbiologic findings, and outcome. Follow‐up was obtained from medical records and telephone contact with primary care veterinarians. Results: Fifty‐two instances of lung lobe torsion were identified in 50 dogs, with a median follow‐up of 453 days (range, 0–3075). Forty‐six (92%) dogs survived to discharge. Dogs with concurrent torsion of the right cranial and middle lung lobes were less likely to survive (2/4) than those with torsion of the left cranial lung lobe (22/22). No other risk factors for mortality prior to hospital discharge were identified. Overall median survival time after hospital discharge was 1369 days. Four dogs had >1 episode of lung lobe torsion. Conclusion: The percentage of dogs surviving to discharge after surgical treatment of lung lobe torsion was higher than previously reported. The short‐ and long‐term prognosis was excellent with surgical treatment of lung lobe torsion. Clinical significance: Surgery should be recommended when lung lobe torsion is suspected because of the high survival to discharge rate and excellent long‐term prognosis.